Load Frequency Controller Tuning Using Chaotic Firefly Algorithm - Chaudhary, Tripti (My University, 2017)
In this work, chaotic firefly has been applied to tune parameters of load frequency controller for multi-area and single area power systems using approximate model matching technique in frequency domain. The error function is minimized by using firefly with chaos by comparing the bode response of actual system model and reference system model. The algorithm was initially validated using 15 unconstrained benchmark functions. After the validation, the algorithm was applied to two single area problems and a two-area problem. The examples were performed for four objective functions with variations in light absorption coefficient and attraction coefficient. The results were performed for five chaotic maps. The results obtained were satisfactory with respect to both single and multi-area power system and convergence characteristics were obtained.
Master of Engineering- Power System
Keywords: Load Frequency Controller; Firefly Algorithm; Chaotic Firefly Algorithm